Toleransi dan kerukunan umat beragama dalam perspektif Al-Qur`an dan Hadist pada pelaksanaan sholat Idul Adha di Depok - Qurrota`ayun, Itasyafa (Maliki Interdisciplinary Journal, 2026)
Tolerance is an essential value in the social life of a pluralistic society. this attitude emerges as an effort to prevent conflict and maintain harmony. in islamic perspective, tolerance serves as a fundamental principle in establishing peaceful relations among religious communities. differences within society often create potential tension, making mutual respect and understanding crucial.This study employs a qualitative approach using the library research method by examining hadith collections, book, journals, and relevant scholarly woeks. The primary data are sourced from Qur’anic verses and hadiths that emphasize peaceful coexistence and mutual respect. The findings reveal that Islamic teachings emphasize not only theological tolerance but also its practical implementation in daily life. This can be seen un the eid al-adha prayer practices in depok, where cooperation and respect among different religious groups are cleary demonstrated, where non-muslim residents actively maintain security and order during prayers.Islam teaches that living peacefully and honoring differences is a key principle for creating a harmonious and stable society.